Layer-modulated synthesis of uniform tungsten disulfide nanosheet using gas-phase precursors. Issue 4 (31st October 2014) - Park, Jusang; Lee, Wonseon; Choi, Taejin; Hwang, Sung-Hwan; Myoung, Jae Min; Jung, Jae-Hoon; Kim, Soo-Hyun; Kim, Hyungjun
Abstract : We describe a synthesis process of WS2 nanosheets with layer controllability and high uniformity using chemical vapor deposition (CVD) and WCl6 and H2 S as gas-phase precursors. Abstract : The synthesis of layered transition-metal-disulfide (MS2, M = Mo, W) nanosheets with layer controllability and large-area uniformity is an essential requirement for their application in electronic and optical devices. In this report, we describe a synthesis process of WS2 nanosheets with layer controllability and high uniformity using chemical vapor deposition (CVD) and WCl6 and H2 S as gas-phase precursors. Through this process, we can systematically modulate the thickness of WS2 nanosheets by controlling the duration of the reaction between WCl6 and H2 S. The CVD-grown WS2 nanosheets exhibit good stoichiometry as well as dependencies of a clear Raman shift and bandgap on the number of layers. These properties are confirmed by X-ray photoemission spectroscopy, Raman spectroscopy, and photoluminescence measurements. The number of layers of WS2 nanosheets is confirmed by atomic force microscopy. Finally, we demonstrate the fabrication and performance of a photodetector based on a hybrid structure consisting of graphene and a WS2 nanosheet.